TGFB2 and BCL2L11 methylation in male laryngeal cancer patients - Shen, Zhisen (Oncol Lett, 2016)
DNA methylation is a major regulatory mechanism of gene expression. The aim of the present study was to test the association of transforming growth factor β2 (TGFB2) and B cell lymphoma 2-like 11 (BCL2L11) gene methylation with the risk of laryngeal squamous cell carcinoma (LSCC). Using bisulfite pyrosequencing technology, DNA methylation levels of TGFB2 promoter and BCL2L11 gene-body CpG cytosines were measured in 90 LSCC tissues and 90 adjacent normal tissues. Analysis of variance and paired sample t-test were used to determine the association of gene methylation and the risk of LSCC. Our results revealed that there were no differences in TGFB2 and BCL2L11 methylation levels between the LSCC tissues and the paired normal tissues (P>0.05). Further breakdown analyses demonstrated that the association results of the two gene methylation levels and LSCC remained unchanged with the age, smoking history, histological differentiation or clinical stage of the LSCC patients (all adjusted P>0.05). In conclusion, there is no association of TGFB2 promoter and BCL2L11 gene-body methylation with the risk of LSCC in males.